PERANCANGAN DAN PENGEMBANGAN JARINGAN VLAN PADA DILI INSTITUTE OF TECHNOLOGI (DIT) TIMOR LESTE MENGGUNAKAN PACKET TRACER - Jeronimo Guterres, Lilia Ervina; Triyono, Joko; Nurnawati, Erna Kumalasari (Jurnal Jarkom, 2014)
ABSTRACTVirtual LAN (VLAN) is a network of networks that are connected together despite different locations to do with the configuration of the equipment switch trunking method, the switch can be connected to the network router to connect a specified VLAN. This research will design a virtual network environment LAN in Dili Institute Of Tecnhology (DIT) Timor Leste provide results that can improve perfroma VLAN network, the distribution network based on the existing department, enabling administrators to manage the network, minimizing costs, and security methods.In the trials conducted on two network design is to test connectivity, data transmission and download / upload, on each VLAN to know the results of the average and will be compared with two network design and good where it will be used.Â Keywords: VLAN, Trunking Switch, Router